Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Di Puskesmas Simolawang Surabaya - Muhajir, Achmad; Haniwijaya, Silvia; Andriani, Dewi (Journal of Health Management Research, 2025)
Background: Based on the results of observations, we found that there were complaints or patient dissatisfaction regarding medical services, namely patient registration queues, pharmacy services, waiting times for medicines at the Simolawang Surabaya Community Health Center. Aims: The objective of this research is to identify patient satisfaction with the quality of service at the Simolawang Surabaya Community Health Center. Methods: This research uses quantitative methods with a cross-sectional research design. With a sample of 55 respondents, sampling using Simple Random Sampling. Results: The research results show that there is a significant influence between service quality and patient satisfaction, the significance value is very low (0.000). Shows that there is a significant influence between service quality on patient satisfaction. The quality of service at the Simolawang Surabaya Community Health Center can be considered very effective in creating high satisfaction among patients who utilize the facilities and services at the Simolawang Surabaya Community Health Center. Conclusion: Based on this, effectiveness measurements are carried out through patient satisfaction surveys and service quality assessments. This approach not only produces high levels of satisfaction, but also reflects ongoing efforts to improve the quality of health services for the community.